In-situ growth Ru / TiOx electrode and application thereof as chlorine evolution catalyst

By growing TiOx in situ on the foamed titanium matrix and loading Ru nanoparticles to form Ru/TiOx catalysts, the problem of the existing chlorine-eliminated catalyst coating is solved, and catalytic performance with higher stability and lower overpotentiality is achieved. It is suitable for the anode material of hypochlorous acid generators.

CN119736666APending Publication Date: 2025-04-01UNIV OF JINAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510035176.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing chlorine-eliminated catalysts are prone to coating peeling problems during long-term use, which affects their stability and service life.

Method used

By growing TiOx in situ on the foamed titanium matrix and loading Ru nanoparticles, the Ru/TiOx catalyst is formed. The porous structure of the foamed titanium foam provides rich growth sites for the crystal growth of metal oxides, and grow deeply into the matrix material to avoid coating peeling.

Benefits of technology

The catalyst is achieved with higher stability and lower overpotential performance, better than commercial DSA electrodes, suitable for the anode material of hypochlorous acid generators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736666A_ABST
    Figure CN119736666A_ABST
Patent Text Reader

Abstract

The invention particularly relates to an in-situ growth Ru / TiOx electrode and application of the in-situ growth Ru / TiOx electrode as a chlorine evolution catalyst. The preparation method of the electrode material comprises the following steps: placing highly clean foam titanium in a high-concentration hydrochloric acid solution, heating in an oil bath pan, placing the treated foam titanium in a hydrochloric acid solution containing RuCl3 for hydrothermal reaction, and cleaning and drying the reacted sample to obtain the Ru / TiOx electrode. The overpotential of the electrode material for electrocatalytic chlorine evolution in a sulfuric acid solution containing 1 M of NaCl and having a pH value of 1 is 50 mV, and the electrode material has good chlorine evolution capability and excellent stability and is expected to be applied to a hypochlorous acid generator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chlorine evolution catalysts, in particular to an in-situ grown Ru / TiO x The Ru / TiO electrode x The invention relates to a method for preparing an electrode and an application of the electrode as a chlorine evolution catalyst. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] As a highly efficient, (micro) residual chlorine-containing disinfectant, hypochlorous acid has been widely accepted internationally, especially when it is prepared by electrolysis rather than chemical mixing. Since the purity of the raw materials can be better controlled and the presence of "impurities" is reduced, hypochlorous acid can theoretically be used as a safer and more environmentally friendly disinfection product for a wide spectrum of use, which is the direction and trend of sterilization technology. The hypochlorous acid generator can electrolyze an aqueous solution containing chloride ions (such as sodium chloride solution), apply voltage to the anode and cathode in the electrolytic cell, and cause water molecules and chloride ions to undergo a redox reaction to generate hypochlorous acid (HClO). Among the commercial hypochlorous acid generators, DSA (Dimensionally Stable Anode) is currently the most widely used anode. It is usually based on titanium and coated with a precious metal oxide coating on the surface. It has good electrocatalytic activity, conductivity, oxidation resistance and corrosion resistance. However, during long-term use, the DSA electrode may have the problem of coating shedding, affecting its stability and service life.

[0004] In order to maintain the stability of the catalyst, the method currently commonly used is to use surface coating or doping with other elements while maintaining high chlorine evolution catalytic activity. In the research and development of anode materials for hypochlorous acid generators, exploring highly active and stable catalysts has become a hot topic in the research of anode materials for hypochlorous acid generators. Due to the high utilization rate of active sites, excellent conductivity, and the coordination between metal sites and the matrix, metal oxide mixture-titanium substrate (MMO) electrocatalysts are considered to be the most promising anode materials for hypochlorous acid generators. It is of great significance to provide an anode material with higher catalytic efficiency and more stability. Summary of the invention

[0005] In order to obtain a more stable anode material with higher catalytic efficiency, the present invention is associated with the use of commercial titanium foam as a substrate and titanium source for TiO x TiO was in situ grown on titanium foam by in situ controllable synthesis via hydrothermal reaction, with ruthenium trichloride and hydrochloric acid as active sources and chemical etchants, respectively.x The Ru / TiO x The overpotential of the catalyst in the electrocatalytic chlorine evolution reaction under acidic conditions is 50 mV, and the performance is better than that of the commercial DSA electrode. In addition, the catalyst prepared by the present invention has a smaller overpotential and superior stability, and is expected to replace the commercial DSA electrode as the anode material of the hypochlorous acid generator.

[0006] Based on the above technical effects, the present invention provides the following technical solutions: In the first aspect, a method for in-situ growth of Ru / TiO is provided. x The electrode is based on titanium foam, and Ru / TiO is grown in situ on the surface and pores of titanium foam. x The nanorods are titanium oxide nanorods with uniformly distributed Ru nanoparticles.

[0007] Existing chlorine evolution catalysts usually adopt the method of preparing a catalyst coating on the surface of a substrate. Common means such as dipping, calcination crystallization or hydrothermal methods make metal crystals with catalytic effect grow on the surface of the anode substrate material to form a catalyst coating. This coating will still gradually peel off as the use time increases, thereby reducing the stability of the generator. In order to overcome the defects in the prior art, the present invention first associates with the use of foamed titanium as a substrate material. Foamed titanium, as a new porous metal material, is usually used in separation and filtration in basic industries such as liquid medicine manufacturing and medical equipment. It has the characteristics of large specific surface area, high strength, and good corrosion resistance. Using it as the substrate material of the anode has the advantages of: first, the rich pore structure of foamed titanium provides abundant growth sites for the crystal growth of metal oxides, and the crystal growth is not only attached to the surface of the substrate, but can penetrate into the interior of the substrate material, effectively overcoming the defects of peeling and instability of the coating-type catalyst. Secondly, the porous structure of titanium foam also has good adsorption properties. The precursor solution containing metal ions can be quickly adsorbed into the pore structure of titanium foam, eliminating the steps of immersing the substrate in the precursor solution or heating and crystallizing in the existing method, effectively simplifying the preparation process.

[0008] In the second aspect, the Ru / TiO x The preparation method of the electrode comprises the following steps: placing the cleaned titanium foam in a high concentration hydrochloric acid solution for heating, placing the treated titanium foam in a precursor solution for hydrothermal reaction, wherein the precursor solution is a Ru-containing 3+ The hydrochloric acid solution is dried after the reaction is completed.

[0009] In the above preparation method, the main purpose of cleaning the titanium foam is to remove surface oil and expose the reaction interface of the titanium foam as much as possible. The cleaning method can be ultrasonic treatment with organic reagents and deionized water in sequence. The present invention provides a feasible implementation method as follows: high-cleanliness titanium foam is obtained by ultrasonic treatment with acetone, ethanol and deionized water for 10 to 20 minutes.

[0010] The main purpose of heating the cleaned titanium foam in a high concentration hydrochloric acid solution is to improve the surface activity of the titanium foam and etch it. The appropriate hydrochloric acid concentration is 15-20wt%, further 16wt%, 17wt%, 18wt% or 19wt%. The heating temperature is 90-120°C, and the preferred method is heating in a hot bath, such as an oil bath.

[0011] Ru in the above precursor solution 3+ The preferred source is a Ru elemental metal salt, such as ruthenium chloride or ruthenium nitrate, more preferably ruthenium chloride (RuCl3), wherein the RuCl3 concentration is 8-15 mM and the hydrochloric acid concentration is 2-5 wt%.

[0012] The temperature of the hydrothermal reaction is 180-220°C, and the reaction time is 18-25h.

[0013] After the hydrothermal reaction is completed, the residual solution on the surface of the reaction product is washed away and then dried to obtain the Ru / TiO x Electrode drying can be carried out by heat radiation drying, negative pressure drying, etc. A specific example is vacuum drying, and the feasible temperature is 60°C~70°C.

[0014] In the third aspect, the Ru / TiO x Application of electrodes as chlorine evolution catalysts.

[0015] The present invention uses the Ru / TiO prepared by the second method x The electrode was electrocatalyzed in an acidic salt solution to precipitate chlorine, and its catalytic performance was investigated. It was verified that the material had good chlorine catalytic efficiency and stability. Therefore, in the third aspect of the present invention, the application of the material as a chlorine evolution catalyst is provided, and the application method is not limited to the Ru / TiO x The electrode serves as an anode of a hypochlorous acid generator.

[0016] Therefore, in the fourth aspect, a hypochlorous acid generator is provided, wherein the generator anode uses the Ru / TiO x electrode.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for in-situ growth of TiO on titanium foam. xThe invention relates to a chlorine evolution electrocatalyst loaded with Ru nanoparticles and a preparation method thereof. The preparation process of the method is simple, pollution-free and has abundant raw materials. The prepared electrocatalyst has high chlorine evolution performance and excellent stability. The catalyst can be used as an anode material for a hypochlorous acid generator device, and its catalytic performance is better than that of a commercial DSA electrode. The study of chlorine evolution by hydrothermal synthesis can provide a reference for the application of hypochlorous acid generator devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0019] Figure 1 The Ru / TiO synthesized in Example 1 x The morphological characterization results; in, Figure 1 (a) TEM image; Figure 1 (b) HRTEM lattice fringes; Figure 1 (c) is the Ti element distribution image; Figure 1 (d) is the O element distribution image; Figure 1 (e) is the Ru element distribution image; Figure 2 The Ru / TiO prepared in Example 1 x Photo of contact angle with electrolyte; Figure 3 The Ru / TiO prepared in Example 1 x Catalyst electrochemical performance test results; Figure 3 (a) LSV curve of 1 M NaCl added to sulfuric acid solution at pH = 1; Figure 3 (b) Figure 3 (a) Comparison of the Tafel slopes of the obtained materials; Figure 3 (c) Prepared Ru / TiO x Comparison of impedance performance between the electrode and commercial DSA electrodes; Figure 3 (d) Prepared Ru / TiO x Comparison of switching frequency performance between the electrode and commercial DSA electrodes; Figure 4 The Ru / TiO prepared in Example 1 x Electrode stability test experiment. DETAILED DESCRIPTION

[0020] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0021] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0022] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0023] Example 1 In this embodiment, an in-situ growth Ru / TiO x Electrode and preparation method thereof: The titanium foam was cleaned with acetone, ethanol, and deionized water in turn to remove the surface oil and obtain highly clean titanium foam. The cleaned titanium foam was placed in an 18wt% hydrochloric acid solution in an oil bath at 90°C for 15 minutes. After being rinsed with deionized water, it was placed in a 3wt% hydrochloric acid solution of 10 mM RuCl3 and transferred to a reactor for hydrothermal reaction at a hydrothermal temperature of 200°C and a reaction time of 20h. The reacted material was washed with deionized water and dried in vacuum at 60°C to obtain a product recorded as Ru / TiO x electrode.

[0024] Example 2 In this embodiment, another method for in-situ growth of Ru / TiO is provided. x Electrode and preparation method thereof: The titanium foam was washed with acetone, ethanol and deionized water in turn to remove the surface oil and obtain highly clean titanium foam. The cleaned titanium foam was placed in a 15wt% hydrochloric acid solution in an oil bath at 100°C for 12 minutes. After being rinsed with deionized water, it was placed in a 2wt% hydrochloric acid solution of 8 mM RuCl3 and transferred to a reactor for hydrothermal reaction at a hydrothermal temperature of 180°C and a reaction time of 25 hours. The reacted material was washed with deionized water and vacuum dried at 65°C to obtain the Ru / TiOx titanium foam material.

[0025] Example 3 In this embodiment, another method for in-situ growth of Ru / TiO is provided. xElectrode and preparation method thereof: The titanium foam was washed with acetone, ethanol and deionized water in turn to remove the surface oil and obtain highly clean titanium foam. The cleaned titanium foam was placed in a 20wt% hydrochloric acid solution in an oil bath at 120°C for 20 minutes. After being rinsed with deionized water, it was placed in a 5wt% hydrochloric acid solution of 15 mM RuCl3 and transferred to a reactor for hydrothermal reaction. The hydrothermal temperature was 220°C and the reaction time was 18 hours. The reacted material was washed with deionized water and dried in vacuum at 70°C to obtain the Ru / TiO x Titanium foam material.

[0026] Example 4 In this embodiment, a method for in-situ growing Ru / TiO in Example 1 is provided. x A hypochlorous acid generator with an electrode, wherein the anode of the generator is the Ru / TiO x electrode.

[0027] Performance Verification 1. Catalyst morphology The Ru / TiO prepared in Example 1 x TEM, HRTEM and element mapping of the electrode Figure 1 The contact angle with the electrolyte is shown in Figure 2 As shown. TEM observation shows, Ru / TiO x It exists in the form of nanorods, with Ru nanoparticles distributed on the surface of the nanorods. The internal nanoparticles with HRTEM lattice fringe spacing of 0.29 nm and 0.20 nm can be well matched with the (110) crystal planes of Ti and (101) of Ru. In the mapping, the uniform distribution of Ti, O, and Ru elements in the catalyst can be seen, confirming that the Ru particles are uniformly distributed on the titanium oxide nanorods.

[0028] The contact angle is an important parameter for analyzing the wetting properties of liquid on the surface of materials. x Photo analysis of the contact angle with the electrolyte shows that the prepared material has excellent hydrophilicity, which is more conducive to improving the permeability of the electrolyte, thereby increasing the electrochemical reaction rate.

[0029] 2. Electrochemical chlorine evolution performance test All electrochemical tests were performed in a conventional three-electrode system at room temperature in a CHI 760 electrochemical station. A platinum electrode holder, a calomel electrode (Hg / Hg2Cl2) and a graphite rod were used as the working electrode, the reference electrode and the counter electrode, respectively. Linear sweep tests (LSV) and constant voltage tests (IT) were performed in a sulfuric acid solution with pH = 1 and 1 M NaCl. The scan rates of LSV were 5 mV s -1 , the IT test time is 100h.

[0030] The electrochemical performance test results are as follows Figure 3 As shown: Figure 3 (a) Ru / TiO x LSV curves of the electrode and commercial DSA electrode in pH=1 sulfuric acid solution with 1 M NaCl added; prepared Ru / TiO x The catalyst was at 10 mA cm −2 The overpotential at the current density of 1.54 W was 50 mV, which is much lower than that of the commercial DSA electrode (82 mV).

[0031] (b) Tafel slope comparison of the materials obtained in Figure a; prepared Ru / TiO x The catalyst Tafel slope is only 134.7 mV dec −1 , which is lower than that of the commercial DSA electrode (142.3 mV dec −1 ).

[0032] (c) Prepared Ru / TiO x Comparison of impedance performance between the electrode and commercial DSA electrode; prepared Ru / TiO x It has a smaller electrochemical impedance spectroscopy (EIS) of only 4.14 Ω, which is lower than that of commercial DSA electrodes (5.58 Ω), and the electron transfer impedance (R ct ) also reflects the Ru / TiO x Materials are better CER catalysts.

[0033] (d) Prepared Ru / TiO x The conversion frequency performance of the prepared Ru / TiO electrode is compared with that of the commercial DSA electrode. x The transition frequency (TOF) value (for example, 2.03 s at 40 mV) −1 ) is higher than DSA (0.80 s at 40 mV −1 ), indicating that the prepared Ru / TiO x Has better TOF (intrinsic activity).

[0034] 3. Catalyst stability test The above Ru / TiO x The long-term stability test of the electrode adopts the constant voltage method, and the results are as follows Figure 4 After 100 hours of stability testing, there is no significant attenuation of the current density, indicating that the material has good stability.

[0035] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An in-situ growth of Ru / TiO x The electrode is characterized in that With titanium foam as the matrix, Ru / TiOx nanorods are in-situ grown on the surface and in the pores of titanium foam. The nanorods are titanium oxide nanorods with evenly distributed Ru particles.

2. Ru / TiO as claimed in claim 1 x The method for preparing an electrode is characterized in that: The method comprises the following steps: placing the cleaned titanium foam in a high concentration hydrochloric acid solution for heating, placing the treated titanium foam in a precursor solution for hydrothermal reaction, wherein the precursor solution is a Ru-containing 3+ The hydrochloric acid solution is dried after the reaction is completed.

3. Ru / TiO as claimed in claim 2 x The method for preparing an electrode is characterized in that: The foam titanium cleaning is carried out by ultrasonic treatment using organic reagents and deionized water in sequence.

4. Ru / TiO as claimed in claim 3 x The method for preparing an electrode is characterized in that: Highly clean titanium foam was obtained by ultrasonic treatment with acetone, ethanol and deionized water for 10 to 20 min.

5. Ru / TiO as claimed in claim 2 x The method for preparing an electrode is characterized in that: The concentration of the high-concentration hydrochloric acid solution is 15-20wt%, further, 16wt%, 17wt%, 18wt% or 19wt%.

6. Ru / TiO as claimed in claim 2 x The method for preparing an electrode is characterized in that: The heating temperature is 90-120° C., and the preferred method is heating in a hot bath, and more preferably in an oil bath.

7. Ru / TiO as claimed in claim 2 x The method for preparing an electrode is characterized in that: The Ru in the precursor solution 3+ The source is Ru elemental metal salt, preferably RuCl3, the RuCl3 concentration is 8~15mM, and the hydrochloric acid concentration is 2~5wt%.

8. Ru / TiO as claimed in claim 2 x The method for preparing an electrode is characterized in that: The temperature of the hydrothermal reaction is 180-220° C., and the reaction time is 18-25 hours.

9. The Ru / TiO prepared by the method of claim 1 or any one of claims 2 to 8 x Application of electrodes as chlorine evolution catalysts.

10. A hypochlorous acid generator, characterized in that: The anode of the generator is the Ru / TiO x electrode.